A novel bacteriocin isolated from Lactobacillus plantarum W3-2 and its biological characteristics - Wang, Zengguang; Zhang, Yixuan; Chen, Chengcheng; Fan, Shichao; Deng, Fangming; Zhao, Lingyan (Frontiers in Nutrition, 2023)
In this study, screening bacteriocin-producing strains from 2,000 plant-derived strains by agar well diffusion method was conducted. The corresponding produced bacteriocin was purified and identified by Sephadex gel chromatography, reversed-phase high-performance liquid chromatography (RP-HPLC), and liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Meanwhile, the biological characteristics of bacteriocin were investigated. The targeted strain W3-2 was obtained and identified as Lactobacillus plantarum by morphological observation and 16S rRNA gene sequence analysis. Correspondingly, a novel bacteriocin (named plantaricin W3-2) produced by L. plantarum W3-2 with a molecular weight of 618.26 Da, and an amino acid sequence of AVEEE was separated, purified by Sephadex gel chromatography and RP-HPLC, and identified by LC-MS/MS. Further characteristics analysis displayed that plantaricin W3-2 had good thermal, pH stability, and broad-spectrum antimicrobial ability. In conclusion, plantaricin W3-2 can be used as a new food preservative.